Estudio de factibilidad para la creación de una empresa productora y comercializadora de vino de jamaica en el cantón Yantzaza, provincia de Zamora Chinchipe - Ochoa Pasaca, Miriam Elizabeth (2023)
The project entitled, "Feasibility study for the creation of a producer and marketer of roselle wine in Yantzaza canton, province of Zamora Chinchipe", had the following objectives: to conduct a market study to know the supply and demand and its marketing plan; to develop a technical study to determine the size, location and engineering of the project and the legal and administrative organization of the company; a financial study to know the investment and financing; finally the financial evaluation to determine the feasibility or not of the project through financial indicators. The type of research was descriptive exploratory, where the quantitative approach was used, as well as the research techniques that allowed the collection and interpretation of the information. Among the results, the market study determined an unsatisfied demand of 158,568 units of roselle wine; the technical study established an installed capacity of 24,000 units per year, with a market share of 15.14%; the financial study determined an investment of US$40,048.99. To determine the feasibility of the project, it was based on: Net Present Value (NPV) of $28,483.38 obtaining a positive van; the Internal Rate of Return (IRR) is 36.57% higher than the opportunity cost rate; Benefit-Cost Ratio (BCR) of 0.16 cents for each dollar invested; Payback Period (Payback Period) of $28,483.38 for each dollar invested; and the return on investment of $28,483.38 for each dollar invested.